Ficocianina na terapêutica de lesões cutâneas induzidas em ratos envelhecidos - Toniollo, Cleide Luciana (2012)
One of skins main functions is to act like a mechanical barrier to the external environment. The loss, in big proportions, of it s integrity may lead to important changes in homeostasis and even the death of the patient. The scarring process constitutes an immediate and dynamic answer from the organism to the tissue wound with the purpose to restore the anatomic and functional continuity. For the scarring to happen there must be a set of conditions, that include an appropriate nutritional state and a topical therapy. The skin injuries may be defined as any rupture of a tissue or organ integrity, it may reach from the epidermis, that is the most external skin layer, to deeper skin structures like fascia, muscle aponeuroses and cavities organs. The treatment and the caring of skin injuries involve a complex process that goes from the evaluation of the injury to the choice of the appropriate covering favoring the tissue repairing physiology. The tissue regeneration process of the injuries may be accelerated by the use of different therapeutic processes. The being work had as objective to evaluate the therapeutic action of phycocianyn in skin injuries induced in aged rats. For that, forty male aged rats (Wistarhannover) with induced skin injuries were used, they ve been divided in four groups with a n of ten rats, therefore, each received a kind of treatment - G1(Phyococianyn 10%); G2 (Phyococianyn 20%); G3 (Phyococianyn 30%) e G4 (Positive control - Kollagenase®), reference cream. The intervention began on the first day of the postoperative, follow by a period of eighteen days. The rats were subject to a kind of skin injury on the fore back located at the scapulae angle. These injuries were analysed as the scarring contraction, amount of total collagen, fibrosis and inflammatory cells. For the statistical analysis and to perform the comparison between the treatments the Bioestat 5.0 software was used, and to perform the comparison between the parameters the non-parametric test of Kruskal-Wallis was used, to the level of significance of five percent. The results with the phycocianyn cream with different concentrations didn t show significant difference when compared to the Kollagenase® cream (positive control) on the different analysis referring to the concentration taxes of the bloody wounds, and on the values of the total collagen synthesis, inflammation and fibrosis. These results show that phycocianyn present in the cyanobacteriumSpirulinaplatensis may be used in the scarring treatment of skin injuries, seen it s safe profile.